Author Correction: Proteogenomic landscape of human pancreatic ductal adenocarcinoma in an Asian population reveals tumor cell-enriched and immune-rich subtypes (Nature Cancer, (2022), 4, 2, (290-307), 10.1038/s43018-022-00479-7) - Hyeon, Do Young; Nam, Dowoon; Han, Youngmin; Kim, Duk Ki; Kim, Gibeom; Kim, Daeun; Bae, Jingi; Back, Seunghoon; Mun, Dong Gi; Madar, Inamul Hasan; Lee, Hangyeore; Kim, Su Jin; et al. (Nature Cancer, 2023)
Correction to: Nature Cancer. Published online 22 December 2022. In the version of this article initially published, the Acknowledgements section omitted thanks to the Korea Health Industry Development Institute (grant no. HI16C2037 to T.P.) funded by the Ministry of Health & Welfare. The error has been corrected in the HTML and PDF versions of the article.